Limbic-Predominant Age-Related TDP-43 Encephalopathy: Medical and Pathologic Factors Associated With Comorbid Hippocampal Sclerosis. (5th April 2022) - Gauthreaux, Kathryn M.; Teylan, Merilee A.; Katsumata, Yuriko; Mock, Charles; Culhane, Jessica E.; Chen, Yen-Chi; Chan, Kwun C.G.; Fardo, David W.; Dugan, Adam J.; Cykowski, Matthew D.; Jicha, Gregory A.; Kukull, Walter A.; et al.
Abstract : Background and Objectives: Limbic-predominant age-related Tar DNA binding protein 43 (TDP-43) encephalopathy neuropathologic change (LATE-NC) is present in ≈25% of older persons' brains and is strongly associated with cognitive impairment. Hippocampal sclerosis (HS) pathology is often comorbid with LATE-NC, but the clinical and pathologic correlates of HS in LATE-NC are not well understood. Methods: This retrospective autopsy cohort study used data derived from the National Alzheimer's Coordinating Center Neuropathology Data Set, which included neurologic status, medical histories, and neuropathologic results. All autopsies were performed in 2014 or later. Among participants with LATE-NC, those who also had HS pathology were compared with those without HS with regard to candidate risk factors or common underlying diseases. Statistical significance was set at nominal p < 0.05 in this exploratory study. Results: A total of 408 participants were included (n = 221 were LATE-NC+/HS−, n = 145 were LATE-NC+/HS+, and n = 42 were LATE-NC−/HS+). Most of the included LATE-NC+ participants were severely impaired cognitively (83.3% with dementia). Compared to HS− participants, LATE-NC+ participants with HS trended toward having worse cognitive status and scored lower on the Personal Care and Orientation domains (both p = 0.03). Among LATE-NC+ participants with Braak neurofibrillary tangle (NFT) stages 0 to IV (n = 88), HS+ participants were more impaired in the Memory and Orientation domains (both p = 0.02). There were no differences (HS+ compared with HS−) in the proportion with clinical histories of seizures, stroke, cardiac bypass procedures, diabetes, or hypertension. The HS+ group lacking TDP-43 proteinopathy (n = 42) was relatively likely to have had strokes ( p = 0.03). When LATE-NC+ participants with or without HS were compared, there were no differences in Alzheimer disease neuropathologies (Thal β-amyloid phases or Braak NFT stages) or Lewy body pathologies. However, the HS+ group was less likely to have amygdala-restricted TDP-43 proteinopathy (LATE-NC stage 1) and more likely to have neocortical TDP-43 proteinopathy (LATE-NC stage 3) ( p < 0.001). LATE-NC+ brains with HS also tended to have more severe circle of Willis atherosclerosis and arteriolosclerosis pathologies. Discussion: In this cohort skewed toward participants with severe dementia, LATE-NC+ HS pathology was not associated with seizures or with Alzheimer-type pathologies. Rather, the presence of comorbid HS pathology was associated with more widespread TDP-43 proteinopathy and with more severe non–β-amyloid vessel wall pathologies.